Response to "A United States shark fin ban would undermine sustainable shark fisheries" D.S. Shiffman & R.E. Hueter, Marine Policy 85 (2017) 138–140. (June 2019) - Porcher, Ila France; Darvell, Brian W.; Cuny, Gilles
Abstract: The paper entitled " A United States shark fin ban would undermine sustainable shark fisheries " (D.S. Shiffman & R.E. Hueter, Marine Policy 85 (2017) 138–140) argues that The Shark Fin Trade Elimination Act of 2017 (HR 1456) and its companion bill in the Senate (S 793), now before Congress in the United States of America, would be counterproductive. We demonstrate that the figures used in support of this claim are inappropriately selected, misinterpreted or incorrect, and that therefore the argument cannot stand. In the face of the extreme depletion of shark numbers globally, the paper fails to give an accurate or objective assessment of the situation.